2015
DOI: 10.1177/0025802415588991
|View full text |Cite
|
Sign up to set email alerts
|

Non-terrorist suicidal death by oral explosion: A rare case from India

Abstract: Suicidal deaths involving explosives are rare. Their occurrence depends on both the availability of materials and the victim's expertise in handling explosive material. We report here a rare case from India of non-terrorist suicidal death involving explosives. The victim was around 25 years old, a blaster by occupation. He committed suicide by detonating dynamite in his mouth. The materials he used to operate this explosion were found near his body at the crime scene. There was characteristic bilateral symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Thirty-four scientific articles dealing with forensic pathology and explosions that fulfilled the inclusion criteria were included in the present research. Among these were 18 case reports [5,13,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], 11 original articles [7-9, 11, 12, 14-16, 38-40], 3 reviews [41][42][43], and 2 case series [44,45]. No technical notes or extensive reviews focused on forensic evaluation of explosions and implications were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-four scientific articles dealing with forensic pathology and explosions that fulfilled the inclusion criteria were included in the present research. Among these were 18 case reports [5,13,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], 11 original articles [7-9, 11, 12, 14-16, 38-40], 3 reviews [41][42][43], and 2 case series [44,45]. No technical notes or extensive reviews focused on forensic evaluation of explosions and implications were found.…”
Section: Resultsmentioning
confidence: 99%
“…The case presented is a further exception, since the possibility to mistake this suicidal event with an accident or homicide relies mainly on circumstantial findings. In the literature of the last thirty years, a few case reports [7,[24][25][26][27][28][29][30][31][32][33][34][35] and one older study from Sweden [39] about selfinflicted explosion deaths have been published. In the cases reported [7,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]39], victims were men, ranging between 20 and 76 years-old (mean 37.7 years), and except for one case (with no risk factors described) [24], all suffered from psychiatric diseases, alcoholism, drug addiction, financial or personal problems [22-36, 39, 44].…”
Section: Self-inflicted Explosion Deathsmentioning
confidence: 99%
“…Davis et al described a case in which a 23-year-old male committed suicide by the creation and denotation of a self-made pipe bomb that exploded while he was resting his neck upon it (6). A case of suicide by intraoral explosion was reported in which the authors conclude that bilateral symmetrical perioral lacerations are considered a characteristic that enables the determination that the death was nonterrorist related (7).…”
Section: Case Of the Monthmentioning
confidence: 99%
“…Within most jurisdictions, suicidal explosions are rarely encountered in the field of forensic pathology. Although a significant number of suicidal explosion deaths are localized to the head (1-7), many cases involve the trunk. As with other explosions, blast injuries can be classified as primary, secondary, tertiary, and quaternary types.…”
Section: Introductionmentioning
confidence: 99%
“…Though, injuries secondary to explosives are seen more commonly in the theater of conflict, deaths due to explosives in the civilian contexts are not common and are seen in industries like the chemical, demolition and mining industries and these are rarely due to fireworks. The civilian population is commonly affected by accidental explosions in mines, road construction, demolition sites, during the use of fireworks, or in related industries [4]. The exact prevalence of deaths due to explosives in the SA population is unknown.…”
Section: Introductionmentioning
confidence: 99%